2020
DOI: 10.1016/j.annonc.2020.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD1 checkpoint inhibitor therapy in acral melanoma: a multicenter study of 193 Japanese patients

Abstract: Background: Acral melanoma (AM) is an epidemiologically and molecularly distinct entity that is underrepresented in clinical trials on immunotherapy in melanoma. We aimed to analyze the efficacy of anti-programmed cell death 1 (anti-PD-1) antibodies in advanced AM. Patients and methods: We retrospectively evaluated unresectable stage III or stage IV AM patients treated with an anti-PD-1 antibody in any line at 21 Japanese institutions between 2014 and 2018. The clinicobiologic characteristics, objective respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(126 citation statements)
references
References 39 publications
10
114
1
1
Order By: Relevance
“…A previous report also suggested that the ORR of anti-PD1 Abs for ALM and mucosal melanoma was lower in a Caucasian population [54]. Taken together, since the ORR of anti-PD1 Abs for advanced ALM in Japanese population was 16.6%, and the PFS and OS for the study cohort were 3.5 months and 18.2 months, respectively [55], the efficacy of anti-PD1 Abs monotherapy for advanced melanoma in the Japanese population was lower than that in the Caucasian population.…”
Section: Efficacy Of Anti-pd1 Antibody Monotherapy Against Advanced Msupporting
confidence: 63%
“…A previous report also suggested that the ORR of anti-PD1 Abs for ALM and mucosal melanoma was lower in a Caucasian population [54]. Taken together, since the ORR of anti-PD1 Abs for advanced ALM in Japanese population was 16.6%, and the PFS and OS for the study cohort were 3.5 months and 18.2 months, respectively [55], the efficacy of anti-PD1 Abs monotherapy for advanced melanoma in the Japanese population was lower than that in the Caucasian population.…”
Section: Efficacy Of Anti-pd1 Antibody Monotherapy Against Advanced Msupporting
confidence: 63%
“…14 More recently, it has been reported across a series of predominantly retrospective studies that the ORR achieved with anti-PD-1 was 14.0-16.6% and the median overall survival (OS) was 18.2-25.8 months in AM patients, and 0-23.2% and 11.5-20.2 months for MM patients, respectively. [15][16][17][18][19][20] In contrast, in the Checkmate067 trial the ORR for nivolumab was 43.7% for all melanoma subtypes, with median PFS 6.9 months and median OS 36.9 months for CM patients. 21 Data thus far suggest that the AM and MM subtypes do not respond as robustly to anti-PD-1 therapy as CM.…”
Section: Introductionmentioning
confidence: 99%
“…The median OS was reported to be 18.1 months, and irAEs of grades 3 to 5 occurred in 27 patients (14.0%). One patient (0.5%) died of grade 5 myasthenia gravis ( 23 ). A study conducted in America involved 50 patients with unresectable stage III or stage IV AM.…”
Section: Resultsmentioning
confidence: 99%
“…Six retrospective studies evaluated nivolumab and pembrolizumab together (14,16,(23)(24)(25)(26). A study involving 21 Japanese institutions evaluated the efficacy of anti-PD-1 antibodies in 193 advanced AM patients.…”
Section: Anti-pd-1 Immunotherapymentioning
confidence: 99%